Potential Therapeutic Effects of Exosomes Packed With a miR-21-Sponge Construct in a Rat Model of Glioblastoma - Monfared, Hamideh; Jahangard, Yavar; Nikkhah, Maryam; Mirnajafi-Zadeh, Javad; Mowla, Seyed Javad (Frontiers in Oncology, 2019)
Glioblastoma multiforme (GBM) is the grade 4 and the most aggressive form of glioma, with a poor response to current treatments. The expression of microRNAs (miRNAs) is widely dysregulated in various cancers, including GBM. One of the overexpressed miRNAs in GBM is miR-21 which promotes proliferation, invasion and metastatic behaviors of tumor cells. With a size of 30-100 nm, the extracellular vesicles “exosomes” have emerged as a novel and powerful drug delivering systems. Recently, exosomal transfer of miRNAs or anti-miRNAs to tumor cells has introduced a new approach for therapeutic application of miRNAs to combat cancer. Here, we have tried to down-regulate miR-21 expression in glioma cell lines, U87-MG and C6, by using engineered exosomes, packed with a miR-21-sponge construct. Our data revealed that the engineered exosomes have the potential to suppress miR-21 and consequently to upregulate miR-21 target genes, PDCD4 and RECK. Interestingly, in cells treated with miR-21-sponge exosomes we observed a decline in proliferation and also an elevation in apoptotic rates. Finally, in a rat model of glioblastoma, administrating exosomes loaded with a miR-21-sponge construct leads to a significant reduction in the volume of the tumors. In brief, our findings suggest a new therapeutic strategy to use engineered exosomes to deliver a miR-21-sponge construct to GBM cells, in order to block its malignant behavior.